Global financial crisis (GFC) and Islamic banks profitability: evidence from MENA Countries /Abdul Mongid. - Mongid, Abdul (Universiti Teknologi Mara Selangor, 2016)
This paper investigate the determinant of profitability of Islamic banks from the MENA region and how Global Financial Crisis (GFC) impacts on their performance. The study covers 117 banks for periods of 2003 to 2011. To examine the determinant of Islamic banking profitability (ROA), we apply a balanced and dynamic panel data regression model. We conclude that the profitability of Islamic banks in the MENA countries is determined positively by asset size, equity to total asset, liquidity risk and negatively by capital adequacy ratio, innovation and global financial crisis. Positive and significant of asset size underlines the viability of economies of scale and scope. Foremost, Dummy for crisis is negative and significant indicating Islamic banks are not immune to the crisis. Innovation should be performed with caution, especially on Off-balancesheet activities.